Optimization of the effort preparation process among the short track female competitors in a year cycle - Lukanova-Jakubowska, A.; Konieczny, M.; Charasna-Blachucik, J.; Wieloch, M. (Central European Journal of Sport Sciences and Medicine, 2015)
The aim of conducted research was an attempt to define the dynamics of aerobic and anaerobic endurance changes in the short track female competitors training during a year cycle which is dependent on the energy characteristic of training burden. Nineteen female competitors of OMKLS Opole club and KU AZS PO Opole, were put through the examination. Eight of them were members of National Team and Olympic Team (Vancouver 2010), moreover, the competitors participated in the World Cup, World Championship, European Championship. The other examined competitors were members of National Team. With the help of terrain and laboratory tests, an official record was made on every lap time, final time of every trial, HR max and HR medium as well as the concentration of lactate in blood in fourth minute after an effort. In the thirtieth minute, after an effort, HR and lactate concentration were registered in order to define the course of restitution. Anaerobic and mixed parameters were examined by the Wingate test in 7.5% load formula of body weight. The results of researches proved that a selection of applied training burdens was not conductive to the adaptation of process according to the Mathews, Fox model (1976). In the short track, a training burden should reflect the specific of an effort in this discipline, emphasising an anaerobic energy type in a year cycle of preparations.